Study on MCFC-integrated GSCC systems with SEGR in parallel or series and CO2 capture - Bian, Jing; Duan, Liqiang (Frontiers in Energy Research, 2023)
In this paper, two new molten carbonate fuel cell (MCFC)-integrated gas–steam combined cycle (GSCC) systems with selective exhaust gas recirculation (SEGR) and CO2 capture are proposed and analyzed. The CO2 concentration in the gas turbine emission is increased because CO2 is selectively recycled with the help of SEGR. Molten carbonate fuel cells (MCFCs) are another way to increase CO2 concentration in the gas turbine flue gas by translating only CO2 from the cathode to the anode. In these two new gas–steam combined cycle systems, SEGR connected with MCFC, either in parallel or series, increases CO2 concentration beyond 11%. A gas–steam combined cycle system combined with MCFC and CO2 capture without SEGR is used as the reference system. Aspen Plus software is adopted to build the system models, and the performances of different systems are discussed and compared. The research results reveal that for the MCFC-integrated gas–steam combined cycle system with SEGR in series and CO2 capture, the CO2 concentration of gas turbine exhaust increases to 11.72% and the thermal efficiency is 56.29% when the overall CO2 capture rate is 88.16%, which is 1.13% higher than that of the reference system; for the MCFC-integrated gas–steam combined cycle system with SEGR in parallel and CO2 capture, the CO2 concentration of gas turbine exhaust increases to 14.15% and the thermal efficiency is 56.62%, which is 1.46% higher than that of the reference system. Furthermore, the economic analysis results show that the economic performances of new systems are mainly influenced by MCFC cost and will be gradually improved with the decrease in the MCFC cost.